The effect of replacing specialty protein sources with synthetic amino acids in phase 2 nursery-pig diets - Frantz, N.Z.; Tokach, Michael D.; Nelssen, Jim L.; DeRouchey, Joel M.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A 28-d growth study with a total of 1,500 pigs (7 d after weaning and 14.5 lb initial BW) was conducted to compare differences in pig performance when fed either fish meal, poultry meal, or synthetic amino acids in a phase 2 nursery-pig diet. In addition, pigs were fed either a negative-control diet (predominately soybean meal without specialty protein sources) or a positive-control diet containing both blood meal and fish meal. Spray-dried whey was added to all diets at 10% and fat was added at 3%. All diets were formulated to meet minimum amino acid ratios. From d 7 to 17, feeding pigs the positive-control diet or the diet high in synthetic amino acids resulted in improved ADG and F/G (P<0.01), compared with those of pigs fed the negativecontrol, fish-meal, or poultry-meal diets. Pigs fed the positive-control diet or the synthetic amino acid diet were heavier at d 17 (P<0.01) than were pigs fed the negative control or diets containing fish or poultry meal. There was no treatment effect on ADFI (P>0.34). When all pigs were fed a common diet from d 17 to 35, similar ADG and F/G were observed between all dietary treatments (P>0.17); but pigs fed the positive-control diet had increased ADFI (P<0.01) compared with that of the negative control or of diets containing fish meal, poultry meal, or synthetic amino acids. For the overall treatment period (d 7 to 35), pigs fed the positive-control diet had greater ADG (P<0.01) and were heavier (P<0.01) than were pigs fed the negative-control diet or fed diets containing fish meal or poultry meal; the performance pigs fed the diet containing high concentrations of synthetic amino acids was intermediate. Pigs fed the positive-control diet also had increased ADFI (P<0.01), compared with that of pigs fed the other dietary treatments. Pigs fed the diet containing high concentrations of synthetic amino acids or the positive-control diet tended to have improved F/G (P<0.07), compared with that of pigs fed the other dietary treatments. In summary, synthetic amino acids were an effective replacement for specialty protein sources, such as fish meal or poultry meal, in the phase 2 diet.
Keywords: Swine; Pigs; Protein sources; Synthetic amino acids; Weanling pigs